Ada 2012 Reference Manual. Language and Standard Libraries International Standard ISO/IEC 8652/2012 (E) - Taft, S. Tucker; Duff, Robert A.; Brukardt, Randall L.; Ploedereder, Erhard; Leroy, Pascal; Schonberg, Edmond; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The Ada 2012 Reference Manual is an enhanced version of the text of International Standard ISO/IEC 8652/2012(E) for the programming language Ada. The Ada 2012 Reference Manual combines all of the previous corrections of Technical Corrigendum 1 and Amendment 1 with changes and additions that improve the capabilities of the language and the reliability of programs written in the language. The Ada 2012 Reference Manual will replace the former versions as an indispensable working companion for anybody using Ada professionally or learning and studying the language systematically.
General -- Lexical Elements -- Declarations and Types -- Names and Expressions -- Statements -- Subprograms -- Packages -- Visibility Rules -- Tasks and Synchronization -- Program Structure and Compilation Issues -- Exceptions -- Generic Units -- Representation Issues -- The Standard Libraries -- Annex A (normative) Predefined Language Environment -- Annex B (normative) Interface to Other Languages -- Annex C (normative) Systems Programming -- Annex D (normative) Real-Time Systems -- Annex E (normative) Distributed Systems -- Annex F (normative) Information Systems -- Annex G (normative) Numerics -- Annex H (normative) High Integrity Systems -- Annex J (normative) Obsolescent Features -- Annex K (informative) Language-Defined Aspects and Attributes -- Annex L (informative) Language-Defined Pragmas -- Annex M (informative) Summary of Documentation Requirements -- Annex N (informative) Glossary -- Annex P (informative) Syntax Summary -- Annex Q (informative) Language-Defined Entities -- Index.
Keywords: Computer science; Software engineering; Operating systems (Computers).; Computer Science; Programming Techniques; Programming Languages, Compilers, Interpreters; Operating Systems; Software Engineering